Pengaruh Takaran Kompos dan Konsentrasi Pupuk Organik Cair Terhadap Pertumbuhan dan Hasil Cabai Rawit (Capsicum Frutescens L.) - Duta Waskita, Faishal; Maria Theresia, Darini; Widata, Sri (Universitas Sarjanawiyata Tamansiswa, 2022)
The purpose of this study was to determine the effect of compost and liquid organic fertilizer concentration on the growth and yield of cayenne pepper (Capsicum frutescens L.). The research was conducted in Mandungan 1 Hamlet, Margoluwih Village, Kec. Seyegan, Kab. Sleman, Special Region of Yogyakarta. The research method used a factorial Completely Randomized Block Design (RAKL), with three replications, 10 combinations so that 30 plant plots were obtained from all combinations and replications. The first factor tested was compost S1 = compost 5 tons per ha, S2 = compost 10 tons per ha, S3 = compost 15 tons per ha. The second factor tested was liquid organic fertilizer C1 = 0.1 percent concentration, C2 = 0.2 percent concentration, C3 = 0.3 percent concentration and control = Urea 30 g, KCl 30 g, TSP 40 g. The observed growth and yield variables included plant height, number of branches, leaf area, leaf weight, plant fresh weight, plant dry weight, age of flowering, number of fruit planted, weight of fruit planted and weight of fruit in plots. The treatment of various types of compost and POC doses showed that there was a significant difference in the growth and yield of cayenne pepper plants. The treatment of compost dose and liquid organic fertilizer concentration showed that there was a significant difference in the number of branches and the yield of cayenne pepper. There is an interaction between the type of treatment with the dose of compost and the concentration of liquid organic fertilizer on the variable fruit weight per hectare. The treatment with 10 tons of compost per hectare with a POC concentration of 0.3% (S2C3) resulted in the highest fruit weight per hectare. The control treatment showed no significant difference to the growth and yield variables.